Process, precedent, and community : new learning environments for engineering design - Holland, Dónal (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2014)
Project-based design courses are an increasingly conunon component of engineering education. Most engineering schools have traditionally emphasized the analytical and scientific aspects of the discipline, and an increase in practical and experiential learning represents a transformation of established approaches to teaching in these institutions. However, there are significant challenges to developing and delivering these courses. Minimal guidance is available to educators who face these challenges. In particular, there is a paucity of research aligning learning objectives with pedagogical theories and practical guidelines. This thesis makes a contribution to both research and practice in engineering design education. A pedagogical framework for a particular type of project-based engineering design course is developed. The framework is intended to guide the development and evaluation of learning environments for these courses. It consists of learning objectives in the form of essential design knowledge, learning theories that align with each of these objectives, and practical guidelines for course design. The pedagogical framework is initially developed through a review of previous research on design cognition and of learning theories from the fields of educational psychology and social anthropology. The framework is subsequently used in three phases of participant observer research in project-based design courses at two universities. During each phase of research, the framework is used to guide the interpretation of results, and the results are in turn used to expand the framework to include guidelines for the development and improvement of learning environments. The expanded framework provides guidance in improving subsequent course iterations. Thus, the learning environments and the pedagogical framework evolve in parallel throughout the research.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin